Converting sago by-product into kraft paper / Wan Samiati Andriana W. Mohamad Daud … [et al.]. - W. Mohamad Daud, Wan Samiati Andriana; Muhammad Azmi, Safrina (2009)
Abundant sources of sago bark and fibre of extracted sago flour does not bring significant momentary economics to the farmers although the locals use the barks of the trunk as timber fuel, wall materials, ceilings and fences and fibre of extracted sago flour as animal feed. The processed into Kraft paper used a simple natural process. The Kraft paper can be used an innovative media in new surfaces for painters in their artwork and handicraft paper for gift wraps, fhoto frames and gift boxes. The utilities of this by-products reduces the enviromental pollution.